Trearments of Water and Manure From the Buffaloes on Growth and Production of Some Rice (Oryza sativa) Varietas - Simatupang, Lambok; Hanum, Chairani; Hanum, Hamidah (Jurnal Online Pertanian Tropik, 2019)
The research objectives were to find out the growth responses and the results of providing water treatment and manure from buffaloes to C/N which is different from the rice plant variety. The rice was planted in a pot arranged in a greenhouse. The water treatment consisted of two treatment phases, namely irrigation with interval and continuous irrigation. The provision of manure from buffaloes consisted of without treatment, with treatment of C/N 19, 80:1 and treatment of C/N 10, 15:1. The varieties studied were Inpari 1, Inpari 13, Siramos and Siboru Tambun. The results showed that water treatment had positive influence on the plant development which was significantly seen in the height of plant and the number of plantlet and panicle. The best irrigation was indicated by the irrigation with interval. The provision of manure from buffaloes had influence on the number of plantlet per cluster which was indicated very significantly by 40 HST, significantly by 20HST, and very significantly by 40 and 60 HST; and on the number of panicle per cluster which was indicated significantly by 60 HST and very significantly by 100 HST filled grains, and on the number of empty grains per cluster, indicating positive influence.